Investigation of the Level and correlates of Happiness among the Students of Qom University of Medical Sciences in 2017, (Iran) - Meysam Hoseini Amiri; Mohamad Abbasi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2018)
Background and Objectives: There is some evidence that happiness may be affected by the cognition under the influence of physical and social environment of a person’s habitat. The purpose of this study was to assess the level and correlates of happiness among paramedical, nursing and midwifery students of Qom University of Medical Sciences.   Methods: This descriptive cross-sectional study was conducted on 343 eligible students of paramedicine, nursing and midwifery schools of Qom University of Medical Sciences in 2017. The subjects were entered into the study through multistage random sampling method. The data were collected using demographic and Oxford Happiness questionnaires. Data were analyzed using independent t-test, one-way analysis of variance, and Pearson and Spearman correlation tests.   Results: The mean score of happiness was obtained 38.5±13.3 for paramedical students and 36.2±16.7 for nursing and midwifery students. According to the result of independent t-test, there were significant differences between the score of happiness and marital status, age, and educational level (p<0.05). Also, the result of one-way ANOVA showed a significant difference between score of happiness and students’ education major (p=0.003). According to the result of Pearson test, there was a direct and significant correlation between age and happiness score of the students (r=0.146, p=0.007).   Conclusion: The results of the present research revealed that paramedical, nursing and midwifery students of Qom University of Medical Sciences had an acceptable level of happiness. The variables of age, gender, educational grade, and major, were also known as the correlates of happiness.